Perancangan Antarmuka Sistem Informasi Kependudukan Desa Pandanarum Kec. Pacet Kab. Mojokerto dengan Metode Human-Centred Design (HCD) - Elistya Maghfiroh; Satrio Hadi Wijoyo; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Pandanarum Village Head's Office is an office which located at the frontier of two villages in Pandanarum Village, Mojokerto Regency, especially on Pacet Subdistrict. The Village Head's Office performing population record activities on its administration. On the recording of its populations, the Village Office doesn't have a good data structure yet and inefficient recap process that affects the overall evaluation performance of the population when Village Head need data immediately. Based on the problems in this research, it inflicts the Village Head can't give the right decision for village development. This research produces interface design that focuses on the user's perspective and their needs to increase data recording efficiency and providing information to Head Office at Pandanarum Village Office using Human-Centred Design (HCD) method. There are several phases in HCD, there are understanding and specify the context of usage, specify the user requirements, produce design solution and evaluating the design of wireframe and high fidelity prototypes. The features are based on accordance with user requirements and then evaluating design solution qualitatively through direct interviews with users to meet user needs and consist of user agreement. This research result interface designs, 9 improvement recommendations and interface design that have been improved.